A study of total optimisation model for supply balance in electric power market network. (4th April 2019) - Sun, Jing; Mori, Yuna; Nakade, Koichi
This paper aims to derive optimal combination of electric powers for supply balance of electric power market network. As traditional combination of electric powers, hydro, fuel and nuclear power are developed in order to provide electricity for modern living in a stable manner at the lowest prices. Recently, due to the problems of CO2 emissions, fuel price increase and safety measures of nuclear power plants, the increase of renewable energy in energy mix became an important issue of electric power industry. In this paper, first, an electric supply model for calculating the optimal energy mix considered with safety, economy and environment is proposed, then, a total optimisation stochastic model for supply balance considered electric power supply capacity and reliability is developed, finally, a case study of Japan power market is conducted. The results of numeric experiment show that the proposed models are useful for setting of the optimal energy mix.